Potential development of poultry feed industry in Central Halmahera Regency, North Maluku Province - Nurhasanah Nurhasanah; Sariffudin Fatmona; Johan Fahri; Ida Hidayanti; Yusri Sapsuha (Agrikan: Jurnal Agribisnis Perikanan, 2022)
The poultry feed industry is one of the industries that has the potential to be developed. A descriptive feasibility study was conducted to examine the development of the poultry feed industry in Central Halmahera Regency, North Maluku Province, based on socio-cultural and socio-economic conditions. This study was conducted in Central Halmahera Regency from May to October 2021. The research method consists of preparation, pre-survey, survey, SWOT analysis, and socio-economic analysis. The results showed that the development of the animal feed industry in Tilope Village, South Weda District, Central Halmahera Regency, was feasible, while production and marketing were still technically very prospective. The needs for poultry feed so far are still imported from outside North Maluku.